STATUS ANEMIA GIZI BESI DAN KONSUMSI ZAT GIZI PADA ANAK USIA SEKOLAH DI LIMA PANTI ASUHAN DI KOTA DENPASAR - dewi, Melisa; Sutiari, Ketut; Wulandari, lila (ARCHIVE OF COMMUNITY HEALTH; Vol 1 No 1 (2012): Juni (2012)DO - 10.24843/ACH.2012.v01.i01.p06)
Iron de? ciency, anemia, cause a negative impact on health such as lowering levels of endurance, lowering concentration power of learning and child development disorders. This research aims to identify iron de? ciency, anemia, status and nutrient intake in school age children at ? ve orphanages in Denpasar. The design of this research was cross-sectional study conducted at ? ve orphanages in Denpasar. The 48 school age children were assigned using a systematic random sampling. Data of hemoglobin level were coollected using Cyanmethaemoglobin; nutrient intake and iron inhibitors using a SQFFQ and questionnaire. Data were analyzed descriptively and presented in tables and narrative. From examination of 48 samples, results of anemia proportion in school age children at ? ve orphanages amounted to 29.16%. Most sampeles (> 80%) already got su? cient recommended RDA, except for vitamin A that still far below recommended RDA. From 48 of 28 samples (58,33%) have a habit of consuming milk and as many as 38 samples (79,16) consume tea. The conclusion of this study is that school age children are vulnerable to iron de? ciency, anemia, and have the habit of consuming iron inhibitors.
Keywords: Anemia, Iron De? ciency, Nutrient Intake, School-Age Children